2021
DOI: 10.1097/mat.0000000000001555
|View full text |Cite
|
Sign up to set email alerts
|

Premature and Extracorporeal Life Support: Is it Time? A Systematic Review

Abstract: Early preterm birth < 34 gestational weeks (GA) and birth weight (BW) <2 kg are relative contraindications for extracorporeal membrane oxygenation (ECMO). However, with improved technology, ECMO is presently managed more safely and with decreasing complications. Thus, these relative contraindications may no longer apply. We performed a systematic review to evaluate the existing literature on ECMO in early and late (34–37 GA) prematurity focusing on survival to hospital discharge and the complication intracrani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 110 publications
(289 reference statements)
0
3
0
Order By: Relevance
“…There is accruing evidence regarding current age (<34 weeks’ gestation) and weight (<1.7–2 kg) exclusion criteria for ECLS, suggesting they be reconsidered under special circumstances. A systematic review of all premature patients treated with ECLS demonstrated that survival rates for premature babies with CDH supported with ECLS, although rarely offered, were similar to survival in the prematurely born infant with CDH without ECLS 89 90. The most recent ELSO dataset demonstrates an overall survival of 50% (n=7564), with a modest decline in infants <34 weeks’ GA (44%); survival is even lower in those infants <2 kg (29%).…”
Section: Resultsmentioning
confidence: 99%
“…There is accruing evidence regarding current age (<34 weeks’ gestation) and weight (<1.7–2 kg) exclusion criteria for ECLS, suggesting they be reconsidered under special circumstances. A systematic review of all premature patients treated with ECLS demonstrated that survival rates for premature babies with CDH supported with ECLS, although rarely offered, were similar to survival in the prematurely born infant with CDH without ECLS 89 90. The most recent ELSO dataset demonstrates an overall survival of 50% (n=7564), with a modest decline in infants <34 weeks’ GA (44%); survival is even lower in those infants <2 kg (29%).…”
Section: Resultsmentioning
confidence: 99%
“…Gestational age < 34 weeks has since been regarded as a strong relative contraindication for treatment with ECMO. Lately, this has been challenged in a recent review by Mesas Burgos et al 17 . As stated in their review, ECMO treatment has improved significantly over the past decades, with a lower rate of ICH complication and higher survival in early premature patients.…”
Section: Discussionmentioning
confidence: 99%
“…To date, outcome modelling studies on ECMO treated neonates have largely focused on risk factors associated with hemorrhagic stroke, or combined ischemic and hemorrhagic stroke 9 11 . Previous studies suggest that prematurity, pre-ECMO severity of illness, pre-ECMO cardiac arrest and use of veno-arterial (VA) ECMO may be associated with an increase of neurological adverse events in neonates during ECMO support, including BI 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%